2009
DOI: 10.1038/eye.2009.48
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral ptosis correction with mersilene mesh frontalis sling in infants: thirteen-year follow-up report

Abstract: Purpose To assess surgical, visual, refractive, and aesthetic outcomes 13 years after mersilene mesh frontalis sling (MMFS) operation for severe unilateral congenital ptosis performed in 10 infants before 1 year of age. Methods Longitudinal follow-up of an interventional case series by structured ocular examinations, external photographs, and questionnaire-based interviews.Results Mean age at surgery was 6.9±2.7 months. After a mean follow-up of 13.0±0.6 years, one patient (10%) had recurrent ptosis with the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…At the end of the process, 48 publications meeting the eligibility criteria were selected for review ( Fig 1 ). The number of studies included for Fascia Lata were 19 [ 10 28 ], for Mersilene 12 [ 29 , 30 , 22 , 31 , 32 , 25 , 33 – 38 ], for PTFE 5 [ 39 41 , 26 , 42 ] and for Silicon 17 [ 43 – 52 , 13 , 53 , 54 , 20 , 55 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the process, 48 publications meeting the eligibility criteria were selected for review ( Fig 1 ). The number of studies included for Fascia Lata were 19 [ 10 28 ], for Mersilene 12 [ 29 , 30 , 22 , 31 , 32 , 25 , 33 – 38 ], for PTFE 5 [ 39 41 , 26 , 42 ] and for Silicon 17 [ 43 – 52 , 13 , 53 , 54 , 20 , 55 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows characteristics of the studies included [ 15 , 29 , 30 , 32 , 34 – 36 , 38 41 , 51 ]. The time range of the selected studies was 1990[ 38 ]-2015[ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some surgeons advocate very early correction for patients with unilateral congenital ptosis to prevent amblyopia. [22,23] Others prefer delaying ptosis surgery until the child is 4 years old. [24] Because of these factors, the aim of this study was to retrospectively evaluate the visual outcomes and complications of levator resection in patients with unilateral congenital blepharoptosis and determine the optimal time for surgical correction of unilateral congenital blepharoptosis.…”
Section: What This Study Adds To the Fieldmentioning
confidence: 99%
“…[3] As a result, several case series of severe congenital blepharoptosis adopted early correction in infants to prevent occlusion amblyopia and developing strabismus. [7,22,23] Conversely, some authors advocated congenital blepharoptosis need not be corrected early in life because stimulus deprivation due to ptosis presents the least common cause of amblyopia. [2,32,40] Some studies even found postoperative increased astigmatism in eyes that underwent levator resection for unilateral congenital blepharoptosis.…”
Section: Factors Affecting Visual Outcomesmentioning
confidence: 99%
“…2,3 Infection and late recurrence are the 2 disadvantages of using exogenous material for frontalis sling surgery, 4 and some surgeons prefer using autogenous tissue instead. However, some important elements such as lid contour and/or any lid peaking was not included as an outcome measure.…”
mentioning
confidence: 99%